Keterikatan Kerja Dan Beban Kerja Dengan Work Life Balance - Andreani Ratna Sari; Alimatus Sahrah (LPPM Universitas Proklamasi 45, 2023)
ABSTRACT This study aims to determine: 1) the relationship between work engagement and work-life balance for employees, 2) the relationship between workload and work-life balance for employees, 3) jointly between work engagement and workload and work-life balance. life balance for employees. The research sample was 52 employees at Bank X in the Marketing division. The data collection method in this study used the WLB scale, work engagement scale, and workload scale. Data analysis using product moment correlation analysis and multiple linear regression. The results showed: 1) There was a positive relationship between work engagement and Work Life Balance for employees, the correlation was 0.718 (p<0.01); 2) The negative relationship between workload and WLB, obtained a correlation value of 0.654 (p<0.01); 3) The joint relationship between work engagement and workload with WLB obtained an F value of 43.750 and a correlation coefficient of 0.801 (p<0.01) and effective contribution work engagement and workload to WLB is 51 .4% while the remaining 48.6% is influenced by other factors not examined in this study.